PERAN SJAFRUDDIN PRAWIRANEGARA DALAM MEMPERTAHANKAN KEDAULATAN NKRI DARI AGRESI MILITER BELANDA II DI RIAU, TAHUN 1948-1949 - Wijaya, Musri Indra; ', Isjoni; ', Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract. The Independence-Revolution is a term that used in the Third Universe-State to independence-war for the extinct Colonizer-State after the end of second world-war. While it is the Indonesian Revolution-Period was going on 1945-1950's. The one of figured who was being famous at the time was Sjafruddin Prawiranegara. Sjafruddin Prawiranegara was an important figured for Indonesian Republic. He was a staged player, an economist who Indonesia ever had. When the Dutch-Aggression Military II, Sjafruddin Prawiranegara built an Emergency-Government of Indonesian Republic because all head leaders of Indonesia, such as Soekarno, Hatta, and Others were arrested by Dutch. Appearance of an Emergency-Government was to move from one place to another, where was an Emergency-Government mention, over there was the Capital of Its Government, started from West Sumatera until Riau. There are many things that happened in his life during to conduct a guerilla war did not except in Riau. The purpose of this research are, first to be aware about biography of Sjafruddin Prawiranegara. Second, to be aware the effort of Sjafruddin Prawiranegara protected sovereignty of Indonesian Republic from Dutch-Aggression Military II, in Riau on 1948-1949. Third, to be aware the effort of Sjafruddin Prawiranegara after left from Riau. Fourth, to be aware when it Indonesian Republic-Capital back to Yogyakarta. The advantages that required from this research are, first to learn the possession of knowledge. Second, the contribution of intention and give some information as a composition for all of readers to be aware how the roles and efforts that our patriots has done to protect sovereignty of Indonesia from colonization. Third, as input for all sides to be aware the role of Sjarifuddin Prawiranegara to protected sovereignty The Unity of Indonesian Republic-State still awakened till now on.Key Words: Sjafruddin Prawiranegara, Dutch-Aggression Military II, Riau.